(untitled) (Computer Aided Drug Development, 2024)
Author Dr Hymavathi Veeravarapu Associate Professor, Dept of Pharmaceutical Chemistry, Srinivasa Rao college of Pharmacy, Visakhapatnam, Andhra Pradesh, India Abstract The evolution of computers in pharmaceutical research and development (R&D) represents a transformative journey that has revolutionized drug discovery and development processes. From early manual calculations to modern artificial intelligence applications, computational technologies have become integral to pharmaceutical innovation. The advent of personal computers in the 1980s democratized computational capabilities, leading to widespread adoption of computer-aided drug design techniques. The field further advanced with the implementation of molecular dynamics and quantum mechanics simulations, providing unprecedented insights into molecular interactions at atomic and subatomic levels. The introduction of high-performance computing clusters revolutionized data processing capabilities, enabling complex simulations and analyses at scale. Most recently, artificial intelligence and machine learning have emerged as powerful tools for predictive modeling, target identification, and drug optimization. The future trajectory points toward quantum computing and enhanced integration of big data analytics, promising even greater capabilities in drug discovery and development. Keywords: Computational drug design; Molecular dynamics; High-performance computing; Artificial intelligence; Quantum computing View PDF